Adolescent Mental Health During Stay at Home of The Covid-19 Pandemic - Arwan, Arwan; Bayan, Ashfan Abdan; Syam, Sadli; Herawanto, Herawanto; Firmansyah, Firmansyah (Media Publikasi Cendekia Indonesia, 2022)
This study aims to determine and describe the mental health impacts that arise in adolescents during the stay-at-home period of the COVID-19 pandemic. This type of research was a Mix Method with a Sequential Explanatory approach with a Participant Selection model. There were 12 informants in this study consisting of 6 primary informants, 3 key informants, and 3 additional informants. The population in this study amounted to 1000 people with a total sampling technique. The results showed that the highest frequency of each variable was very severe anxiety amounting to 313 people, Normal Stress was 511 people, and normal depression was 548 people. Loneliness, confinedness, academic pressure, parental pressure, family relationships, and fear of infection negatively affect adolescents' mental health. The impact of anxiety on adolescents during the Stay at the home period of the COVID-19 pandemic is feeling fear of contracting COVID-19 either themselves or those close to them. The impact of stress on adolescents during the stay at home period of the COVID-19 pandemic is that it is difficult to focus when online learning, feeling lonely being at home continuously, feel bored at home and feel like they are confined because they can't go anywhere during this pandemic. The impact of depression on adolescents during the stay at home period of the COVID-19 pandemic is that, overall, there are actually few teenagers who appear to be experiencing depression or symptoms of depression